Modernizing Supply Chain through Cloud Adoption: Role of Cloud Enabled Supplier Integration in Gaining Competitive Advantage and Sustainability - Paitoon Chetthamrongchai; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
Cloud computing is deepening its roots in modern day businesses as companies are using it not only for their internal operations but also for suppliers and customers. Cloud enabled supplier integration system is one of the finest examples of such modernization which is being adopting by the firms for better organizational outcomes. However, evidence of such progress is quite rare. This study has targeted to identify the impact of cloud adoption on firm’s sustainability and competitive advantage in mediating role of cloud enabled supplier integration in manufacturing industry of Thailand. Such manufacturing organizations of Thailand were taken in sample which have already adopted cloud system in their firms and 32 such entities’ management was surveyed through questionnaire. Data was afterwards analyzed on AMOS and SPSS for hypotheses testing and screening purposes respectively. Results have confirmed significant positive impact of cloud adoption on firm’s sustainability as well on competitive advantage along with significant mediating role of cloud enabled supplier integration. Originality of this study is inclusion of competitive advantage in model to check its relation with both cloud adoption and cloud integration. Implications of this study are there in paper along with limitations and future research indications.